PENGARUH INTENSITAS PERSEDIAAN DAN PERTUMBUHAN PENJUALAN TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR TAHUN 2018 SAMPAI DENGAN 2022 DI BURSA EFEK INDONESIA - Michael Sinaga; Ramot P Simanjuntak; Juaniva Sidharta (Universitas Kristen Indonesia, 2023)
These studies aim to examine and analyzing effects of inventory intensities and sales growth on tax aggressive in basic industrial and chemical sector company listed from 2018 to 2022 on Indonesia Stock Exchange (IDX). The data collections method use in these studies is secondaries data collections whose data is quantitative in form of financials statements accessed through the official IDX website, namely www.idx.co.id. The sampling techniques in these studies uses non probability sampling techniques with a purposives sampling approach with sample criterias; (1) companies that publish complete and consecutive financial statements from 2018-2022 (2) companies that present their financials statement in Rupiah during research year (3) company that having complete data relate to variable used. These studies use a population of 92 basic industrial and chemical company list on IDX and produced 17 samples during 2018-2022. The data analyst technique used in these studies is multipled linear regression analyst with help of IBM SPSS software version 26. This research was testing use data analyst method include descriptive analyst tests, classical assumption tests, multipled linear regression analyst, hypothesis tests and determination coefficient tests. The results of these studies partially show that inventory intensities have a effects on tax aggressive and sales growth has no effects on tax aggressive. While simultaneously inventory intensities and sales growth have an influence on tax aggressive. Keywords: Tax Aggressive, Inventory Intensities, Sales Growth